Facilitating the implementation of pharmacokinetic‐guided dosing of prophylaxis in haemophilia care by discrete choice experiment. (27th November 2015) - Lock, J.; de Bekker‐Grob, E. W.; Urhan, G.; Peters, M.; Meijer, K.; Brons, P.; van der Meer, F. J. M.; Driessens, M. H. E.; Collins, P. W.; Fijnvandraat, K.; Leebeek, F. W. G.; Cnossen, M. H.; et al.
Abstract : Introduction: Patients', parents' and providers' preferences with regard to medical innovations may have a major impact on their implementation. Aim: To evaluate barriers and facilitators for individualized pharmacokinetic (PK)‐guided dosing of prophylaxis in haemophilia patients, parents of young patients, and treating professionals by discrete choice experiment (DCE) questionnaire. Patients/Methods: The study population consisted of patients with haemophilia currently or previously on prophylactic treatment with factor concentrate ( n = 114), parents of patients aged 12–18 years ( n = 19) and haemophilia professionals ( n = 91). DCE data analysis was performed, taking preference heterogeneity into account. Results: Overall, patients and parents, and especially professionals were inclined to opt for PK‐guided dosing of prophylaxis. In addition, if bleeding was consequently reduced, more frequent infusions were acceptable. However, daily dosing remained an important barrier for all involved. 'Reduction of costs for society' was a facilitator for implementation in all groups. Conclusions: To achieve implementation of individualized PK‐guided dosing of prophylaxis in haemophilia, reduction of bleeding risk and reduction of costs for society should be actively discussed as they are motivating for implementation; daily dosing is still reported to be a barrier for all groups. The knowledge of these preferences will enlarge support for this innovation, and aid in the drafting of implementable guidelines and information brochures for patients, parents and professionals.